PENGARUH KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN PADA PT PLAZA AUTO SERASI GADING SERPONG - Muhammad Mubasyir Aziz; Jakariah (Journal of Research and Publication Innovation, 2025)
The purpose of this study is to determine the influence of product quality and service quality on customer satisfaction at PT Plaza Auto Serasi. The method used is a descriptive method with a quantitative approach. The sampling technique used is Probability Sampling, a sampling method using simple random sampling, namely by using an error level of 10%. Data analysis uses regression analysis, correlation coefficient analysis, determination coefficient analysis and hypothesis testing using the SPSS version 26. The results of this study are that product quality (X1) and service quality (X2) have a positive effect on customer satisfaction (Y) with the regression equation Y = 9.945 + 0.224X1 + 0.576X2 + α. The determination coefficient has a simultaneous effect of 19.2%, The hypothesis test partially obtained a product quality figure of 2,738 tcount > ttable (2,738 > 1,661). Then H0 is rejected and H1 is accepted. This means that there is a positive and significant influence between the independent variables, namely product quality (X1) on customer satisfaction (Y). The quality of service is equal to the tcount > ttable or (4,250 > 1,661). Then H0 is rejected and H2 is accepted. This means that there is an influence between independent variables, namely service quality (X2) on customer satisfaction (Y). The hypothesis test obtained a value of Fcal > Ftabel (10.951 > 2.14). With H0 rejected and H3 accepted, it means that leadership (X1) and motivation (X2) together have a positive effect on employee performance (Y).